2018
DOI: 10.1074/jbc.ra118.005316
|View full text |Cite
|
Sign up to set email alerts
|

Structural disorder in four-repeat Tau fibrils reveals a new mechanism for barriers to cross-seeding of Tau isoforms

Abstract: The intracellular deposition of fibrils composed of the microtubule-associated protein Tau is a characteristic feature of Alzheimer's disease (AD) and other fatal neurodegenerative disorders collectively known as tauopathies. Short Tau fibrils spread intracerebrally through transfer between interconnected neurons. Once taken up by a recipient cell, Tau fibrils recruit Tau monomers onto their ends. Based on the number of microtubule-binding repeats, there are two distinct groups of Tau isoforms: three-repeat (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 73 publications
1
37
1
Order By: Relevance
“…The monomorphic nature of the in vitro 4R tau observed here differs from several recent biophysical studies of 4R tau (46,47). The discrepancy may result from the different protein constructs used as well as differences in the fibril-forming conditions.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The monomorphic nature of the in vitro 4R tau observed here differs from several recent biophysical studies of 4R tau (46,47). The discrepancy may result from the different protein constructs used as well as differences in the fibril-forming conditions.…”
Section: Discussioncontrasting
confidence: 81%
“…The wild-type sequence also shows a broad distance distribution between C291 and C322, suggesting that truncation of the N-terminal half of the protein and/or the fibrillization condition may reduce the structural homogeneity of the fibril core. Another DEER electron paramagnetic resonance study of full-length 2N4R tau fibrils obtained by seeded growth found a broad distance distribution between K311 and I328 (47). Although K311 is exposed to the surface of the β-sheet core in the AD tau structure, within in vitro 4R tau it is located in a spatially constricted region between the β4 and β5 strands.…”
Section: Discussionmentioning
confidence: 99%
“…While we did not see seed-specific detection of tauopathy, as reported by Metrick and colleagues [22,23], using full length substrates we were able to detect seeding activity in 3 R, 4 R, or a 3 R/4 R tauopathy brains diluted up to 1000 fold (Figure 1(b)). This later finding supports those previously reported by of Weismiller et al [26] who demonstrated that the 3 R/4 R tau cross-seeding barrier was reduced when full-length tau (htau40) was used [26]. However, we also found that detection was more selective when substrate and disease isoform were matched, or alternatively, a 3 R/4 R mixture was used (Figures 2(b), 3 (b) and 4(b)).…”
Section: Discussionsupporting
confidence: 92%
“…Because half of the residues in R1 and R2 are different, including the three additional prolines mentioned above, this would come at a higher energetic cost. By contrast, a recent study (Weismiller et al, 2018) has reported that sonicated filaments assembled from 2N4R human tau can seed assembly of monomeric 0N3R tau. It remains to be seen what the structures of those filaments are.…”
Section: Discussionmentioning
confidence: 77%